Quality of life in Italy Research and Reflections - Maggino, Filomena; Nuvolati, Giampaolo; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2012)
The outcome of the first Italian National Conference on Quality of Life, this volume is full of cogent analysis of topics and issues related to well being and quality of life, including focused papers on specific population groupings and discrete themes. Held in Florence in September 2010, the conference saw the creation of the Italian Association of Quality-of-Life Studies, devised as a forum for this varied field of research with a rapidly expanding profile in the context of the continuing financial crisis. The papers address a number of recognized quality-of-life concerns, including public health, wealth distribution, employment, political participation and the perception of crime. Contributors deploy innovative methods of analyzing official statistics that result in more complex and multidimensional indicators. Some papers provide data on other European nations that allow for comparative assessment, while others set out fresh approaches to evaluating quality of life itself. Highly relevant not just to academics, but to policy makers and practitioners in a range of sectors, this publication explores important aspects of a crucial contemporary subject.
Introduction - (Filomena Maggino and Giampaolo Nuvolati) -- I. Quality of Life: Methodological Aspects -- 1. Measuring equitable and sustainable wellbeing in Italy - (Enrico Giovannini and Tommaso Rondinella) -- 2. A Non-Compensatory Approach for the Measurement of the Quality of Life - (Matteo Mazziotta and Adriano Pareto) -- 3. From composite indicators to partial orders: evaluating socio-economic phenomena through ordinal data - (Marco Fattore, Filomena Maggino and Emilio Colombo) -- 4. Light and shade of multidimensional Indexes: how methodological choices impact on empirical results - (Enrica Chiappero and Nadia von Jacobi Nadia) -- II. Quality of Life and Social Change through Italian Official Statistics Social and demographic changes in Italy - (Linda Laura Sabbadini) -- 5. Satisfied or dissatisfied? An analysis of the results of "Aspects of Daily Life" Italian survey on households - (Silvia Montecolle and Sante Orsini) -- 6. The quality of life measured through the subjective indicators of safety: fear, worry about crime and the risk of criminality - (Maria Giuseppina Muratore, Alessandra Federici and Daria Squillante) -- 7. Hours of work and life quality - (Maria Clelia Romano and Daniele Spizzichino) -- III. Quality of Life, Public Administration and Civil Society -- 8. Civic evaluation as a tool for analysing and achieving quality of life under the citizen$1 (Bs point of view - (Angelo Tanese and Alessio Terzi) -- 9. Security, quality of life and development. A holistic approach - (Maurizio Sajeva) -- 10. Democracy and Public Knowledge. An Issue for Social Indicators - (Paolo Parra Saiani) -- 11. Flexicurity and Workers Well-Being in Europe: Is Temporary Employment Always Bad? - (Federica Origo and Laura Pagani) -- IV. Health Related Quality-of-Life -- 12. From a concept's evolution analysis to the definition of a new methodological evaluation tool of Health Related Quality-of-Life (HRQoL) questionnaires - (Francesca Ierardi, Lisa Gnaulati, Stefania Rodella and Elena Ruviglioni) -- 13. The use of Health Related Quality of Life measures in Official statistics: the Italian experience - (Lidia Gargiulo, Laura Iannucci and Alessandra Tinto) -- 14. Individual and family quality of life in intellectual disability: a challenging relationship - (Marco Bertelli, Annamaria Bianco, Daniela Scuticchio and Ivan Brown).s
Keywords: Social sciences; Quality of Life; Statistics; Quality of Life -- Research; Social Sciences; Quality of Life Research; Statistics, general